A framework for integrating wastewater-based epidemiology and public health - Brosky, Hanna; Prasek, Sarah M.; Innes, Gabriel K.; Pepper, Ian L.; Miranda, Jasmine; Brierley, Paul E.; Slinski, Stephanie L.; Polashenski, Lois; Betancourt, Walter Q.; Gronbach, Katie; Gomez, Diana; Neupane, Reshma; et al. (Frontiers in Public Health, 2024)
Wastewater-based epidemiology (WBE) is an environmental approach to monitor community health through the analysis of sewage. The COVID-19 pandemic catalyzed scientists and public health professionals to revisit WBE as a tool to optimize resource allocation to mitigate disease spread and prevent outbreaks. Some studies have highlighted the value of WBE programs that coordinate with public health professionals; however, the details necessary for implementation are not well-characterized. To respond to this knowledge gap, this article documents the framework of a successful WBE program in Arizona, titled Wastewater Analysis for Tactical Epidemiological Response Systems (WATERS), detailing the developed structure and methods of communication that enabled public health preparedness and response actions. This communication illustrates how program operations were employed to reduce outbreak severity. The structure outlined here is customizable and may guide other programs in the implementation of WBE as a public health tool.